Specific Binding of Peroxidase-Labeled Myelin Basic Protein in Allergic Encephalomyelitis - Johnson, Anne B. (1971)
A conjugate of horseradish peroxidase and the encephalitogenic basic protein from myelin has been used to study the antigen reactivity of tissue in the autoimmune disease, experimental allergic encephalomyelitis. Control conjugates were also prepared of peroxidase and bovine serum albumin and of peroxidase and lysozyme, another basic protein. The basic protein from myelin conjugate was specifically bound by lymph node cells from rabbits immunized against the basic protein. Some of these cells appeared to be plasma cells. The conjugate was also specifically bound by occasional cells in the spinal-cord infiltrates of animals with early signs of allergic encephalomyelitis. These cells resembled large lymphocytes and plasma cells. There was no difference between the binding of basic protein of bovine and rabbit origin. The findings suggest the possibility that a local release of antibody within the target organ may play a role in the pathogenesis of allergic encephalomyelitis.